Identification of a major immunogenic region of equine herpesvirus-1 glycoprotein E and its application to enzyme-linked immunosorbent assay - Andoh, Kiyohiko; Takasugi, Maaya; Mahmoud, Hassan Y.A.H.; Hattori, Shiho; Terada, Yutaka; Noguchi, Keita; Shimoda, Hiroshi; Bannai, Hiroshi; Tsujimura, Koji; Matsumura, Tomio; Kondo, Takashi; Maeda, Ken (Veterinary microbiology, 2013)
A major immunogenic region of equine herpesvirus (EHV)-1 glycoprotein E (gE) was identified. Firstly, the various fragments of EHV-1 gE were expressed as fusion proteins with glutathione S-transferase (GST) in Escherichia coli and their antigenicities were compared by immunoblot analysis using sera from horses experimentally infected with EHV-1. Thirty-three amino acids of gE (a.a. 169–201) specifically and sensitively reacted with the antibodies induced by EHV-1 but not EHV-4 infection. The corresponding region of EHV-4 gE (a.a. 169–199) did not react with antibodies to EHV-1, indicating that this region is specific for each virus. In addition, when the antigenicities of three 20-mer synthetic peptides of EHV-1 gE, gE1(169–188), gE1(176–195) and gE1(182–201) were compared by enzyme-linked immunosorbent assay (ELISA), gE1(169–188) was found to contain a major B-cell epitope. ELISA using two synthetic peptides, gE1(169–188) and gG4(319–330), previously identified as the major EHV-4-specific epitope in gG, was developed and could specifically detect antibodies to EHV-1 and EHV-4, respectively. In Japan, the EHV-1 deleted in gE gene (EHV-1 ΔgE) virus is expected to be introduced in the field as a new modified live vaccine. This ELISA did not react with antibodies induced by inoculation with EHV-1 ΔgE, indicating that it is a useful method to differentiate between EHV-1 infection and EHV-1 ΔgE inoculation. In conclusion, the ELISA described herein, using synthetic peptides, is a simple method to distinguish between EHV-1 and EHV-4 infections and will be suitable as a vaccine marker after introduction of EHV-1 ΔgE into field horses.